Menstrual Taboo in the Perspective of Young Women and Men - Agnieszka Swend (Fabrica Societatis)
The article presents the results of aqualitative study conducted with agroup of 14 participants (7women and 7men) and focuses on their perception of the phenomenon of menstruation from asocial perspective. The aim of the analysis was to determine whether the views expressed by young individuals are similar to the dominant discourse on menstruation. To understand the opin-ions of young people, aqualitative method was employed, and partially structured interviews were conducted. The participants in the study were individuals born between 1996 and 2004. The main conclusion drawn from the obtained responses is that young individuals perceive menstrual taboos as still prevalent, especially among older generations, but they also observe acertain emerging change. Despite the common treatment of menstruation as ataboo subject, the younger generation tends to challenge these beliefs. The study focused on the perspective of young participants because their views are becoming increasingly visible in the public sphere. It is worth noting that the study also considered the perspective of men, who also influence the way menstruation is perceived, and their viewpoint is often overlooked. The article presents how menstruation is currently portrayed and discusses some of the historical and religious reasons that contributed to its stigmatization. The anal-ysis incorporates one of Émile Durkheim’s sociological theories regarding social facts.